G215 Ecmo and audiological follow up in children. (25th October 2020) - Cockburn, CS; Davidson, M; Donnelly, P; Matta, N; Wylie, G; Law, M; Sasaki, Y
Abstract : Introduction: Children who have been supported with extracorporeal membrane oxygenation (ECMO) require follow-up including neurodevelopmental screening and audiological assessment. Hearing screening or audiometry is also included within the Extracorporeal Life Support Organization (ELSO) recommendations for the care of children post-ECMO. Methods: A retrospective survey was sent to families of children who were supported on ECMO run between 2008 and 2017 in a large paediatric ECMO centre. The aim of this questionnaire was to enquire about their experiences, follow up and any hearing or neuro-developmental difficulties their children had experienced. Families were also asked if their children had undergone hearing screening after hospital discharge. The central and local notes (if available) of these children were reviewed to look for evidence of audiological assessment. Results: 146 surveys were sent out with 64 families responding representing a 43.8% return rate. Thirty four of the families who responded (53%) report their children had hearing screening after ECMO. Seven families (11%) expressed concern about their children's hearing. There was evidence of hearing screening in the medical notes of only 28% responders (18 children). Most of these were not planned assessments due to the history of ECMO. The children undergoing hearing screening were referred due to concerns such as speech delay and recurrent ear infections. Forty four percent of children (8/18) had documented hearing screening because of their previous ECMO run. Conclusions: Over half of children who have had an ECMO run were reported by their parents to have had hearing screening completed though there was only documentation of the results in 28% of those where it was said to be undertaken. In the cases of documented audiological assessment, 56% of these were due to concerns raised out with routine post-ECMO assessment. It is important to raise awareness of the hearing screening requirement in children after ECMO and look at implementing a robust system to ensure this takes place. The responsibility for ensuring this takes place should lie with the ECMO centre.